The impact of IT adoption in SMEs supply chains: A case of Gauteng and Free State provinces of South Africa - K. Mathu; M. T. Tlare (South African Journal of Business Management, 2017)
This study probed the influence of information technology adoption by small and medium enterprises (SMEs) in Gauteng and Free State Provinces of South Africa. The supply chain integration and collaboration of the SMEs was also explored to ascertain the IT influence. A quantitative methodology was used as it was the best way to measure the extent of the information technology (IT) influence. The participants were sent questionnaires via the e-mail and provided feedback to the researcher via the same medium. The sample size of 300 comprised the owner/manager in the manufacturing and service sector SMEs from the two provinces. The data collected was analysed using a Confirmatory Factor Analysis (CFA) method and Structural Equation Modelling (SEM) using AMOS 22 Statistical Analysis software. The findings from the study indicated that information technology adoption enhanced integration and collaboration of SMEs supply chain. It also emerged that there was wide application of information technology amongst most of the SMEs approached. The other benefits that emerged from the increased use of IT in the supply chain included enhancement of customer service, inventory management, lead time, and relationship building. Indeed, Instilling IT skills to the SMEs employees was actually knowledge enhancement in performing business tasks.
Keywords: 650